2009
DOI: 10.1029/2008jb005908
|View full text |Cite
|
Sign up to set email alerts
|

Principles of volcanic risk metrics: Theory and the case study of Mount Vesuvius and Campi Flegrei, Italy

Abstract: [1] Despite volcanic risk having been defined quantitatively more than 30 years ago, this risk has been managed without being effectively measured. The recent substantial progress in quantifying eruption probability paves the way for a new era of rational science-based volcano risk management, based on what may be termed ''volcanic risk metrics'' (VRM). In this paper, we propose the basic principles of VRM, based on coupling probabilistic volcanic hazard assessment and eruption forecasting with cost-benefit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 25 publications
2
67
0
Order By: Relevance
“…Nevertheless, such achievement product is necessary for urban planning and risk reduction on the territory. In particular, a significant improvement of the risk mitigation strategies is enabled by the quantitative combination of the probability distributions for the spatial location of the eruptive vent originating the PDC, the size of the flow, and the temporal estimates for such expected event in the future (see Woo, 1999;Marzocchi and Woo, 2009;Rougier et al, 2013;Wadge and Aspinall, 2014). This accomplishment is the main purpose of this research study.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such achievement product is necessary for urban planning and risk reduction on the territory. In particular, a significant improvement of the risk mitigation strategies is enabled by the quantitative combination of the probability distributions for the spatial location of the eruptive vent originating the PDC, the size of the flow, and the temporal estimates for such expected event in the future (see Woo, 1999;Marzocchi and Woo, 2009;Rougier et al, 2013;Wadge and Aspinall, 2014). This accomplishment is the main purpose of this research study.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the approach has been further developed by Bebbington and Zitikis (2016) to place it into a time-dependent framework which considers the time windows between effective changes in the eruption probability, the call of an evacuation and its completion, further evolution (either increasing or decreasing) in eruption probabilities, the actual eruption occurrence, and citizens' dislocation and their return to the affected areas. In a retrospective application to the 1631 sub-Plinian eruption of Vesuvius, they found that the eruption probability value justifying the evacuation call turns out to be 13% lower than for the "static" approach by Marzocchi and Woo (2009). Translated into the reconstructed time evolution of the eruption probability, that difference would have anticipated an evacuation call by six days.…”
Section: Making Decisionsmentioning
confidence: 99%
“…50 %) make the evaluation of the exposure clearer to decision-makers and the identification of the potential losses faster for governments. The acceptable levels of risk required to compile isomass maps are of complex identification (Marzocchi and Woo 2009;Villagrán de León 2006).…”
Section: Discussionmentioning
confidence: 99%